Healthcare Workforce Performance in the Era of Digital Transformation: The Role of Digital Competence, Technostress, and Employee Engagement - Diana diana; Abu Yazid (Economics and Digital Business Review, 2026)
Digital transformation in the healthcare sector requires healthcare workers to possess adequate digital competence and manage technology-related pressures. This study examines the effects of digital competence and technostress on healthcare workforce performance, with employee engagement as a mediating variable. A quantitative associative approach was employed using questionnaire data collected from 184 healthcare workers in hospitals across the DKI Jakarta region. Data were analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The findings reveal that digital competence has a positive and significant effect on employee engagement but does not significantly affect healthcare workforce performance. Technostress does not significantly influence employee engagement, yet it has a positive and significant effect on performance. Employee engagement neither significantly affects performance nor mediates the relationships between digital competence, technostress, and healthcare workforce performance. The model explains 54.3% of the variation in performance. These findings highlight the importance of balancing digital competence enhancement and the management of technology-related pressures to support successful digital transformation and improve healthcare workforce performance.